MULTIBAHASA DALAM KONTEN INSTAGRAM: ALIH KODE, CAMPUR KODE, DAN CITRA DIRI - Hasyar, Dwi Rahmiati; Hendrawan, Wawan; Budiarti, Any (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study scrutinizes the use of multilingualism, namely English, Javanese, and Indonesian, in the content reels uploaded by Bella Amelia on her Instagram account, @kartikabelaa. Specifically, this research examines the 'forms' of code-switching and code-mixing that occurred in Bella Amelia's conversations with her imaginary child character named Kenzo. In addition, it also observes how these language variations are used to reflect Bella Amelia's identity or self-image. This study employed a descriptive qualitative approach to understand the phenomena of code-switching, code-mixing, and Bella Amelia's self-image. The data were taken from 5 samples of reel contents and were selected using a purposive sampling technique to select contents that reflect the language phenomena under scrutiny. The results revealed that 52 code-switching and 146 code-mixing were found in Mami and Kenzo's conversations in 5 Instagram Reels content uploaded by the @kartikabellaa account. Furthermore, the code-switching and code-mixing were classified into 31 situational code-switching, 21 metaphorical code-switching, 79-word code-mixing, 33-phrase code-mixing, and 34-clause code-mixing. The self-image displayed by Bella Amelia in her Instagram content generally tries to build an ideal and humorous self-image, as well as a social and inspirational self-image. Keywords: Multilingualism, Code-Switching, Code-Mixing, Self-Image, Instagram Reels